1995
DOI: 10.1111/j.1365-2923.1995.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

A skin cancer training programme: evaluation of a postgraduate training for family doctors

Abstract: This study aimed to evaluate the effectiveness of a postgraduate skin cancer training programme in improving family doctors' levels of knowledge and clinical practice. Forty-one of 59 family doctors (69% consent) who enrolled in the training programme agreed to participate in its evaluation. Approximately half of the doctors were allocated to the 'intervention' group, and the others were in the 'waiting-list' control group. Pre-and post-test data were collected to assess changes in doctors' knowledge, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The RCTs included used a variety of educational interventions including lectures, videos, and an internet triage package. 18,19,21,22 The interventions were compared to control groups that received no intervention. They were of mixed quality and provided inconsistent evidence.…”
Section: Intervention Typementioning
confidence: 99%
See 4 more Smart Citations
“…The RCTs included used a variety of educational interventions including lectures, videos, and an internet triage package. 18,19,21,22 The interventions were compared to control groups that received no intervention. They were of mixed quality and provided inconsistent evidence.…”
Section: Intervention Typementioning
confidence: 99%
“…The two studies that reported a positive outcome of improved diagnosis and management did not see the improvement continue to the end of the study period. 21,22 Overall, studies rated as high quality reported poorer outcomes than those rated as low quality, and positive outcomes were only seen in the short term.…”
Section: Intervention Typementioning
confidence: 99%
See 3 more Smart Citations